Role of the Intracellular Sodium Homeostasis in Chemotaxis of Activated Murine Neutrophils - Najder, Karolina; Rugi, Micol; Lebel, Mégane; Schröder, Julia; Oster, Leonie; Schimmelpfennig, Sandra; Sargin, Sarah; Pethő, Zoltán; Bulk, Etmar; Schwab, Albrecht (Frontiers in Immunology, 2020)
The importance of the intracellular Ca2+ concentration ([Ca2+]i) in neutrophil function has been intensely studied. However, the role of the intracellular Na+ concentration ([Na+]i) which is closely linked to the intracellular Ca2+ regulation has been largely overlooked. The [Na+]i is regulated by Na+ transport proteins such as the Na+/Ca2+-exchanger (NCX1), Na+/K+-ATPase and Na+-permeable, transient receptor potential melastatin 2 (TRPM2) channel. Stimulating with either N-formylmethionine-leucyl-phenylalanine (fMLF) or complement protein C5a causes distinct changes of the [Na+]i. fMLF induces a sustained increase of [Na+]i, surprisingly, reaching higher values in TRPM2-/- neutrophils. This outcome is unexpected and remains unexplained. In both genotypes, C5a elicits only a transient rise of the [Na+]i. The difference in [Na+]i measured at t = 10 min after stimulation is inversely related to neutrophil chemotaxis. Neutrophil chemotaxis is more efficient in C5a than in an fMLF gradient. Moreover, lowering the extracellular Na+ concentration from 140 mM to 72 mM improves chemotaxis of WT but not of TRPM2-/- neutrophils. Increasing the [Na+]i by inhibiting the Na+/K+-ATPase results in disrupted chemotaxis. This is most likely due to the impact of the altered Na+ homeostasis and presumably NCX1 function whose expression was shown by means of qPCR and which critically relies on proper extra- to intracellular Na+ concentration gradients. Increasing the [Na+]i by a few mmol/l may suffice to switch its transport mode from forward (Ca2+-efflux) to reverse (Ca2+-influx) mode. The role of NCX1 in neutrophil chemotaxis is corroborated by its blocker, which also causes a complete inhibition of chemotaxis.